Security and Privacy in Communication Networks 9th International ICST Conference, SecureComm 2013, Sydney, NSW, Australia, September 25-28, 2013, Revised Selected Papers - Zia, Tanveer; Zomaya, Albert; Varadharajan, Vijay; Mao, Morley; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2013)
This book constitutes the thoroughly refereed post-conference proceedings of the 9th International ICST Conference on Security and Privacy in Communication Networks, held in Sydney, Australia, in September 2013. The 26 revised full papers presented were carefully reviewed and selected from 70 submissions. The papers are grouped in topical sections on: security and privacy in mobile, sensor, and ad hoc networks; malware, botnets, and distributed denial of service; security for emerging technologies: VoIP, peer-to-peer, and cloud computing; encryption and key management; security in software and machine learning; network and system security model; security and privacy in pervasive and ubiquitous computing.
Security & amp; Privacy in Mobile, Sensor and Ad Hoc Networks -- Malware, Botnets and Distributed Denial of Service -- Security for Emerging Technologies: VoIP, Peer-to-peer and Cloud Computing -- Encryption and Key Management -- Security in Software and Machine Learning -- Network and System Security Model -- Security and Privacy in Pervasive and Ubiquitous Computing ATIS 2013: 4th International Workshop on Applications and Techniques in Information Security.
Keywords: Computer science; Computer Communication Networks; Data protection; Data encryption (Computer science).; Computer Science; Systems and Data Security; Computer Communication Networks; Data Encryption; Computers and Society; Information Systems Applications (incl. Internet).